Structural Isomers: Small Change with Big Difference in Anion Storage - Dai, Huichao; Chen, Yuan; Cao, Yueyue; Fu, Manli; Guan, Linnan; Zhang, Guoqun; Gong, Lei; Tang, Mi; Fan, Kun; Wang, Chengliang (Nano-Micro Letters, 2023)
Organic electrode materials are promising for batteries. However, the reported organic electrodes are often facing the challenges of low specific capacity, low voltage, poor rate capability and vague charge storage mechanisms, etc. Isomers are good platform to investigate the charge storage mechanisms and enhance the performance of batteries, which, however, have not been focused in batteries. Herein, two isomers are reported for batteries. As a result, the isomer tetrathiafulvalene (TTF) could store two monovalent anions reversibly, deriving an average discharge voltage of 1.05 V and a specific capacity of 220 mAh g−1 at a current density of 2 C. On the other hand, the other isomer tetrathianaphthalene could only reversibly store one monovalent anion and upon further oxidation, it would undergo an irreversible solid-state molecular rearrangement to TTF. The molecular rearrangement was confirmed by electrochemical performances, X-ray diffraction patterns, nuclear magnetic resonance spectra, and 1H detected heteronuclear multiple bond correlation spectra. These results suggested the small structural change could lead to a big difference in anion storage, and we hope this work will stimulate more attention to the structural design for boosting the performance of organic batteries. Highlights: 1 The effect of small changes in isomers on electrochemical performance have not been focused in batteries and two isomers are reported for Zn-ion batteries here. 2 The isomer tetrathiafulvalene (TTF) could store two monovalent anions reversibly, showing remarkable performance that outperformed most of the reported organic electrode materials for zinc-ion batteries. 3 The isomer tetrathianaphthalene (TTN) could only reversibly store one monovalent anion and upon further oxidation, it would undergo an irreversible solid-state molecular rearrangement to TTF.